Caribbean Artistic Genealogies of Withdrawal. Rethinking Caribbean Visuality Beyond Objecthood - Garrido Castellano, Carlos (2017)
This essay examines how Caribbean artists have employed withdrawal in critical, insurgent ways. I confront several Caribbean projects developed in different chronologies and locations that have attempted to use withdrawal in order to challenge uneven institutional dynamics. The examples I discuss here – Cuban art dedicates itself to baseball (Havana, José A. Echevarría Stadium (Vedado), 1989), Silvano Lora’s Marginal Biennial (Santo Domingo, multiple locations, 1992), Joëlle Ferly’s L’Art de faire la grève (Martinique, Fondation Clément, 2009) and L’Artocarpe (Guadeloupe, ongoing) – problematize the role of artistic agency, the reach of the exhibition form and the influence of foreign expectations. Traditionally, Caribbean art has been subjected to a process of commodification and exoticization. Through the examination of those four practices, I will assert that an alternative genealogy of active, productive interventions concerned with staging emancipative spatial dynamics beyond representational constraints and objecthood can be found.